PENGARUH GENDER DIVERSITY EKSEKUTIF TERHADAP NILAI PERUSAHAAN, TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING : STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2012-2015 - Setia Eka Winasis; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2017)
The aim of this study is to examine the influence of gender diversity of the executive coporate to firm value, with tax avoidance as a mediation variableThe population used in this study consist of mining firms listed at Indonesia Stock Exchange in 2012-2015.The sampling method used in this study is purposive sampling and obtained 87 samples. This study uses simple regression analysis for hypotheses testing.The result of this study show that variable of gender diversity of executive had possitively significant influence on tax avoidance,and gender diversity of executive had negatively significant influence on firm value, while, variables of tax avoidance had no significant influence on firm value. The last, tax avoidance had no influence as mediation variable .